MANAJEMEN PELAKSANAAN DANA BERGULIR SIMPAN PINJAM PEREMPUAN (SPP) OLEH BADAN KERJASAMA ANTAR NAGARI (BKAN) DI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Zaitul Ikhlas; Endry Martius; Faidil Tanjung (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to describe the management of the implementation of Women's Savings and Loans revolving funds and find the factors that cause the implementation of Women's Savings and Loans revolving funds by BKAN in Lembah Gumanti District to continue. The method used in this research is descriptive qualitative by conducting in-depth interviews with key informants and triangulation informants. The results of this study indicate that the management functions consisting of planning, organizing, actuating and controlling have been carried out in accordance with operational standards and procedures (SOP) which are guided by the Solok Regent Regulation Number 26 Year 2016 concerning Protection and Preservation of the Results of the Activities of the Kecamatan Development Program and the Independent Rural Empowerment Community National Program in Solok Regency. The success factor for the SPP revolving fund is due to the use of the Grameen Bank principle, the existence of social capital and social control within the group.